PERTUMBUHAN BIBIT AREN (Arenga Pinnata) PADA PERLAKUAN JENIS DAN DOSIS CENDAWAN ENDOFIT - Aidil Akbar; S Syamsia; Abubakar Idhan (Fapetrik-UMPAR, 2022)
One of the inhibiting factors in providing sugar palm seeds is the dormancy period of sugar palm seeds and the growth of germs that take a long time. This study aims to determine the type of isolate and the application dose of endophytic fungus isolates that can accelerate the growth of sugar palm seedlings. The study was arranged using a Randomized Block Design (RAK) with 2 treatments. The first treatment was the type of endophytic fungus isolate consisting of 3 levels: isolates C1, C2, and C3. The application dose of endophytic fungus isolate consists of 3 levels, namely: 5 g, 10 g, and 15 g. Parameters observed were shoot emergence, plant height, root length, plant fresh weight, fresh root weight, plant dry weight, and root dry weight. The results showed that endophytic fungi isolates C1 and C3 could increase the growth and biomass of sugar palm seedlings, while the best application dose of endophytic fungi was 5 g. Application of endophytic fungi isolates C1 and C3 with a quantity of 5 g increased the growth and biomass of sugar palm seedlings.